Chapter Archeological findings of ancient harbor in the pilot site of Interreg Adrion APPRODI project in Ortona (Ch, Abruzzo), central Adriatic Sea - Zappalorto, Mauro (Proceedings e report, 2020)
The Interreg Adrion 'APPRODI' project aims at a qualitative change in the nature of tourism demand with a transnational approach and at increasing visibility of destinations. the project will allow to create the conditions for development of cultural tourism, even underwater, increasing and enhancing the historical and archaeological resources. The dive samplings allowed to find an important archaeological heritage in the seabeds in front of Ortona coast, testifying to the presence of an ancient port and maritime traffic.